Crime in Northeast Mexico, and its relation to petroleum exploration and production. - Francisco Garcia-Fernandez; Luis Lauro Carrillo Sagastegui; Rafael Alejandro Vaquera Salazar (Norteamérica)
The objective of this work is to establish the relationship between hydrocarbon production and extraction activities in northeast Mexico, including the Burgos Basin and the states of Tamaulipas, Nuevo León, and Coahuila, and the crime rate in these municipalities. Utilizing municipal-level data from 2020, sourced from official sources, a quantitative and cross-sectional methodology is employed in a descriptive study with correlational and spatial analyses. Municipalities with active or inactive hydrocarbon extraction wells were included, representing 73 of the 132 municipalities in the northeastern states. Although the study recognizes inherent limitations due to the collected data volume, which does not allow for categorical affirmation of a causal relationship, it does permit the observation of a trend confirming the correlation between both variables. This opens the door to a more detailed exploration of the effect of oil exploration on crime behavior, considering it as an additional factor that could potentially increase it.